Self-Referenced Memory, Social Cognition, and Symptom Presentation in Autism - Henderson, Heather A. (2009)
BACKGROUND: We examined performance on a self-referenced memory (SRM) task for higher functioning children with autism (HFA) and a matched comparison group. SRM performance was examined in relation to symptom severity and social cognitive tests of mentalizing. METHOD: Sixty-two children (31 HFA, 31 comparison; 8–16 years) completed a SRM task in which they read a list of words and decided whether the word described something about them, something about Harry Potter, or contained a certain number of letters. They then identified words that were familiar from a longer list. Dependent measures were memory performance (d′) in each of the three encoding conditions as well as a self-memory bias score (d′ self-d′ other). Children completed The Strange Stories Task and The Children’s Eyes Test as measures of social cognition. Parents completed the SCQ and ASSQ as measures of symptom severity. RESULTS: Children in the comparison sample showed the standard SRM effect in which they recognized significantly more self-referenced words relative to words in the other-referenced and letter conditions. In contrast, HFA children showed comparable rates of recognition for self- and other-referenced words. For all children, SRM performance improved with age and enhanced SRM performance was related to lower levels of social problems. These associations were not accounted for by performance on the mentalizing tasks. CONCLUSIONS: Children with HFA did not show the standard enhanced processing of self- vs. other-relevant information. Individual differences in the tendency to preferentially process self-relevant information may be associated with social cognitive processes that serve to modify the expression of social symptoms in children with autism.